“Eating Out” Among University Students - Costa,Isabel (2014)
Objective: To compare the Eating Out phenomenon among university students from private and public schools. Methodology: Cross-sectional study conducted among 317 students from private (Biotechnology Faculty) and public (Engineering Faculty) universities aged 19 to 23 years old. Lifestyle variables such as food habits as well as socio-demographic background variables were included in a self-administered structured questionnaire. Results: The proportion of students from the private university who take more than four meals per day is significantly higher than the proportion of students at public university (60.3% vs. 32.1%, p Conclusions: Eating out is frequent among university students. The frequency of consumption of high energy foods suggests that food choices are not the most favourable. Differences between food patterns can be observed when comparing students from a private institution with students from a public one.